2007
DOI: 10.1111/j.1365-3113.2007.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the Sympetrinae (Odonata: Libellulidae): further evidence of the homoplasious nature of wing venation

Abstract: Sympetrinae is the largest subfamily of the diverse dragonfly family Libellulidae. This subfamily, like most libellulid subfamilies, is defined currently by a few wing venation characters, none of which are synapomorphies for the taxon. In this study, we used DNA sequence data from the nuclear locus elongation factor‐1α and the mitochondrial loci 16S and 12S rRNA, together with 38 wing venation characters, to test the monophyly of the Sympetrinae and several other libellulid subfamilies. No analysis recovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
2
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 24 publications
(27 reference statements)
2
38
2
14
Order By: Relevance
“…3). Our results do not entirely comply with other authors (e.g., Rehn, 2003;Pilgrim & Von Dohlen, 2008), who proposed that wing venation is a highly variable region and provides very poor phylogenetic information. Despite the strong selection pressures that flight performance exerted over these structures (Kesel, 2000), homologies were recovered from these structures.…”
Section: Partitioned Analyses Combined Analyses and Phylogenetic Sicontrasting
confidence: 99%
See 2 more Smart Citations
“…3). Our results do not entirely comply with other authors (e.g., Rehn, 2003;Pilgrim & Von Dohlen, 2008), who proposed that wing venation is a highly variable region and provides very poor phylogenetic information. Despite the strong selection pressures that flight performance exerted over these structures (Kesel, 2000), homologies were recovered from these structures.…”
Section: Partitioned Analyses Combined Analyses and Phylogenetic Sicontrasting
confidence: 99%
“…Dijkstra & Vick, 2006;Ware et al, 2007;Pilgrim & von Dohlen, 2008;Blanke et al, 2013), Erythemis was not found as a monophyletic group due to the extensive homoplasy and structural variability observed in its diagnostic characters (Dijkstra et al, 2014). In Ertythemis case, aside from the high intra and interspecific variation that most of the characters showed, a large number of the character states are shared with other genera.…”
Section: Partitioned Analyses Combined Analyses and Phylogenetic Simentioning
confidence: 99%
See 1 more Smart Citation
“…Bechly 1996;. While it may be monophyletic, it does not stand apart from Libellulidae as a whole (Ware et al 2007;Fleck et al 2008b;Pilgrim & von Dohlen 2008). 45.…”
Section: Classificationmentioning
confidence: 99%
“…Carle et al 2008;Dijkstra & Vick 2006;Fleck et al 2008a;Pilgrim & von Dohlen 2008;Ware et al 2007). Moreover, as any potential outgroup of winged insects lacks wings, wing-based phylogenies and classifications (e.g.…”
Section: Introductionmentioning
confidence: 99%